Komunikasi sebagai Upaya Promotor Kesehatan dalam Memelihara Kemitraan di Desa Siaga Aktif Mandiri - Dewi Wulandari; Antono Surjoputro; Syamsulhuda Budi Musthofa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the communication methods Health Promoters use in establishing partnerships in independent, active alert villages in Semarang Regency. This research method uses a qualitative method with a case study approach. The research results show that health promoters communicate with partners through direct meetings, through the media, through village midwives, and in letters. Direct communication aims to maintain good relations. Conclusion: There are 4 Promkes communication techniques, which are good despite shortcomings. Keywords: Independent Active Alert Village, Partnership, Communication, Health Promoter